Analysis of Settlement Induced by Shield Construction of the Metro Passing under Existing Buildings Based on the Finite Difference Method. (28th May 2022) - Wang, Rui; Zhang, Bin; Wang, You
Abstract : A frequent problem when constructing metro tunnels is the uneven settlement of adjacent buildings, which results in huge economic losses. Due to shields causing the settlement of adjacent buildings, this study took the Nantong Metro Line 1 as the research object. The metro runs from the East Huancheng Road Station to the Nantong Intermediate People's Court Station and passes under the old residential area of the Community Sendadi-Huayuan building. Based on the settlement monitoring data, this study analyzed the impact of tunnel shield construction on the foundation settlement of adjacent buildings. The computational analysis of the shield tunnel was performed by numerical simulation, taking into account the upper building load and the construction disturbance to the surrounding rock. Afterward, the study summarized the law behind the settlement. The results show that when the boring machine was tunneling through sandy soil and silt rich in water, its head was prone to twisting due to soil disturbance and the dissipation of pore water, causing instability in the excavation process and eventual ground settlement. In the sandy strata, the relationship between foundation settlement caused by shield construction and time can be approximated as an exponential function in a certain area. The vibrations from shield excavation caused the foundations to vibrate for a short period of time. Therefore, the average settlement of buildings directly above the underpass reached 7 mm/d. Likewise, the tunneling shield caused a 1.5 mm settlement before passing under the building. It caused a peak settlement of 4.0 and 5.1 mm during and after passing under the buildings, respectively. The width of the settlement troughs of approximately 7D formed after the tunnel was excavated. Shield excavation placed the soil at the top of the excavation face in a state of tensile stress, causing tensile and shear damage to the soil and forming a local plastic zone.